Influence of coffee drinking and cigarette smoking on the risk of primary late onset blepharospasm: evidence from a multicentre case control study. Issue 8 (19th June 2007) - Defazio, G; Martino, D; Abbruzzese, G; Girlanda, P; Tinazzi, M; Fabbrini, G; Colosimo, C; Aniello, M S; Avanzino, L; Buccafusca, M; Majorana, G; Trompetto, C; et al.
Abstract : Prior coffee and smoking habits were investigated in a multicentre case control study involving 166 patients presenting with primary late onset blepharospasm (BSP), 228 hospital control patients with primary hemifacial spasm and 187 population control subjects from five Italian centres. Information on age at disease onset, smoking and coffee drinking status at the reference age and average number of cups of coffee drunk/cigarettes smoked per day reached high and similar test–retest reproducibility in case and control patients. Unadjusted logistic regression analysis yielded a significant inverse association of prior coffee drinking and cigarette smoking with case status for the control groups. After adjustment for age, sex, referral centre, disease duration, years of schooling and ever coffee drinking/cigarette smoking, as appropriate, the smoking estimate lacked significance whereas the association of coffee intake and BSP did not (cases vs hospital control patients: OR 0.37 (95% CI 0.20 to 0.67); cases vs population control subjects: OR 0.44 (95% CI 0.23 to 0.85)). The strength of the inverse association between BSP and coffee intake tended to increase with the average number of cups drunk per day. There was a significant correlation between age of BSP onset and number of cups per day (adjusted regression coefficient 1.73; p = 0.001) whereas no correlation was found with number of packs of cigarettes per day. Coffee drinking may be inversely associated with the development of primary BSP and this association may partly depend on the amount consumed.